A bibliometric analysis of dengue-related publications in the Science Citation Index Expanded. (September 2016) - Ho, Yuh-Shan; Siu, Evelyn; Chuang, Kun-Yang
Dengue is a re-emerging infection that poses significant threat to about half of the world's population, but there was little information on the bibliometric trend and patterns of dengue research globally. The purpose of this research is to provide a bibliometric analysis of dengue research from 1991 to 2014, and to assess the relationship between the burden of dengue and scientific publications. Most papers were classified under the topics of tropical medicine, virology, infectious diseases, parasitology or immunology. India may soon surpass Thailand in the ranking. Overall, international collaboration appeared to play a significant role in dengue research. Regional specificity of dengue may also influence the bibiliometric profile of dengue research. Nevertheless, dengue research output appeared to be positively and significantly related to the level of dengue cases, an indication that the scientific community was responding well to the needs of the population.